ChemInform Abstract: Synthesis and Structural Characterization of New Bifunctional o‐Hydroxyacetophenones — Potential Linker Molecules for Coordinative Framework Construction. Issue 29 (1st July 2013) - Huebscher, Joerg; Guenthel, Michael; Rosin, Robert; Seichter, Wilhelm; Mertens, Florian; Weber, Edwin
Abstract Two new linker‐type molecules (Ia, b) are synthesized.